Beginning Office 365 Collaboration Apps Working in the Microsoft Cloud - Mercurio, Ralph (Apress, 2018)
Start making the most of the latest collaboration tools in Office 365-including email, SharePoint, OneDrive, Office Web Applications, and Planner-and integrate them into your team's projects to boost productivity, engagement, innovation, and enjoyment at work. This book walks you through the features, teaching you how to choose the right tools for your situation, and how to combine them with your favorite non-Microsoft collaboration platforms such as Slack and Trello. While technologies for collaboration are more advanced than ever before, there also are more of them. Beginning Office 365 Collaboration Apps will help you make sense of what is available and how it can help you and your team be more productive. Real-world examples show you how collaboration can solve business problems. What You'll Learn: Know the collaboration features available across the Office 365 stack, and how to choose the ones that are right for you and your team in any given situation Understand the software-as-a-service (SaaS) model and how it enables users to be more productive and effective Discover how multi-device usability and real-time cloud synchronization can help your team collaborate any time, anywhere Find out how Planner can help you manage projects and tasks, even without a project manager Make the most of Delve for advanced, personalized search and discoverability This book is for Office 365 business users with a limited technical background. Readers should be familiar with the Microsoft Office suite products such as Word and Outlook, and work in a team environment. Ralph Mercurio is an IT pro who has specialized in SharePoint and Office for more than 15 years. He was a consultant in New York for NYSE traders, and is currently a government consultant for the state of North Carolina. As an IT pro who has seen many technology changes, he discovered a passion for helping users find ways to leverage what they know to learn a new technology and innovate. With Office 365, he has made it his goal to help readers realize the potential of this powerful platform in order to maximize output and minimize the use of internal resources.